2012
DOI: 10.1073/pnas.1210271109
|View full text |Cite
|
Sign up to set email alerts
|

Using intein catalysis to probe the origin of major histocompatibility complex class I-presented peptides

Abstract: All vertebrate nucleated cells generate peptides from their expressed gene products and then display them at the cell surface bound to MHC class I molecules. This allows CD8 + T cells to detect and eliminate abnormal cells that are synthesizing foreign proteins, e.g., from viruses or mutations. To permit the immune system to more uniformly monitor a cell's proteins, regardless of their half-life or location, it has been thought that the products of rapid degradation of the mistakes of protein synthesis (defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…Between 27% and 70% of these HLA peptides have high DRiPs factors, meaning that a significant portion of them are derived from newly synthesized proteins, which are not only rapidly degraded before their full maturation but possibly also channel some of their degradation products directly to the HLA peptidome (40,41). Large numbers of retirees-derived HLA peptides were also identified in this study, indicating that retirees also contribute significantly to the HLA peptidome (3,39). Different pathways can lead to higher H/L ratios of HLA peptides relative to their source proteins, as discussed in the Introduction.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Between 27% and 70% of these HLA peptides have high DRiPs factors, meaning that a significant portion of them are derived from newly synthesized proteins, which are not only rapidly degraded before their full maturation but possibly also channel some of their degradation products directly to the HLA peptidome (40,41). Large numbers of retirees-derived HLA peptides were also identified in this study, indicating that retirees also contribute significantly to the HLA peptidome (3,39). Different pathways can lead to higher H/L ratios of HLA peptides relative to their source proteins, as discussed in the Introduction.…”
Section: Discussionmentioning
confidence: 66%
“…An ongoing debate in this field deals with the issue whether the MHC peptidome is mostly derived from degradation of mature proteins (retirees) or immature/DRiPs proteins (3,7,24,39). Clear immunological advantage is gained by early warning on pathogen infection through rapid production of MHC peptides from newly synthesized proteins, followed by their immediate presentation at the cells' surface (4,5).…”
Section: Discussionmentioning
confidence: 99%
“…Farfan-Arribas et al (37) used intein catalysis in GFP fusion proteins to demonstrate that antigenic peptides can be generated by protein auto-splicing. Although the authors concluded that the intein-generated peptides must derive from retirees, spliced antigenic peptide-containing fragments are clearly abundant in their pulse-chase experiments (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Despite claims to the contrary [163], this is not controversial. Peptide generation from native proteins was first clearly shown using influenza A virions to deliver internal virion proteins to the cytosol under conditions where viral proteins cannot be synthesized [33].…”
Section: Drips ؉ Retirees ‫؍‬mentioning
confidence: 99%
“…Farfán-Arribas et al [163] cleverly exploited intein catalysis to study peptides that can be created when the peptide-containing intein domain is properly folded. Based on the clear generation of peptides, they concluded that DRiPs play no role in peptide generation.…”
Section: Drips ؉ Retirees ‫؍‬mentioning
confidence: 99%